Optical spectroscopy study of nano- and microstructures fabricated by femtosecond laser pulses on ZnO based systems. Issue 21 (11th May 2018) - de Prado, Esther; Florian, Camilo; Sotillo, Belén; Siegel, Jan; Solis, Javier; Fernández, Paloma
Abstract : Self-organized nanowires with large aspect ratios and beehive-like structures with well preserved luminescence properties. Abstract : The formation of laser induced periodic surface structures (LIPSS) upon irradiation with ultrashort laser pulses at the surface of polycrystalline ZnO based samples, and the potential use of irradiated areas as growth patterns for the production of highly ordered nanostructures have been studied. In particular, pure ZnO, ZnO:Al (5 wt% Al2 O3 ) and ZnO:Mg (5 wt% MgO) samples have been investigated. The surface morphology of the laser fabricated structures depends on the processing parameters, such as energy, number of pulses, repetition rate and laser polarization. Three main types of periodic structures have been formed: LSF (low spatial frequency) and HSF (high spatial frequency) LIPSS and pseudo-spikes (PS). After irradiation, the samples have been used as substrates for vapor–solid growth. It has been found that the growth of micro- and nanostructures in the irradiated regions is much faster than in the non-irradiated ones. Strong differences in the final morphology of the deposited regions are appreciated, not only between irradiated and non-irradiated areas, but also between areas irradiated under different conditions. Scanning electron microscopy (SEM) and cathodoluminescence (CL) measurements at room temperature have been used to monitor the morphology and luminescence properties of the generated structures. For all processed samples, the CL analysis shows a shift of the band edge emission towards higher energies and a lower relative intensity of the defect band in the areas irradiated at higher fluence. The first effect might be attributed to the incorporation of dopants, as already observed for Al and Mg. Yet, the redistribution of defects associated with shallow levels might also be responsible for the observed shift, playing a major role in undoped samples. The decrease in the relative intensity of the defect band can be ascribed to the partial recovery of defects caused by the deposited energy (annealing effect) during the irradiation process.